Refuge and Immigration. Chilean Documentary Cinema Against an Old yet New Dilemma [Refugio E Inmigración. el Cine Documental Chileno Frente a Un Viejo y Nuevo Dilema] - Palomera-Valenzuela, A; Venegas-Valdebenito, H (Universidad Austral de Chile, 2021)
Cinema, both fiction and documentary genres, has a narrative feature that allows to expose points of view, explain, and construct alternative truths. This article is a historical approach to narratives that Chilean documentary cinema has collected from women and men who chose Chile as their destination. The study focuses on audiovisual stories produced in Chile between 2001 and 2019, which, along with capturing experiences, open the possibility of understanding Chilean society and characterize social, political, and cultural behaviors present in it. The stories of migration represented in these audiovisual productions make visible both the existence of critical intersections as narratives of the subjects, contributing from a micro-historical analysis to the social and cultural history and to the visibility of open conflicts of recent history. © 2021, Universidad Austral de Chile. All rights reserved.